PENGEMBANGAN MULTIMEDIA INTERAKTIF “PETOK PEJANDA” BERBASIS APLIKASI PREZI MATERI PERJUANGAN PARA TOKOH PEJUANG PENJAJAHAN BELANDA UNTUK KELAS 5 SDN PULOREJO - Pramita, Fransiska Dwi; Imron, Ilmawati Fahmi; Permana, Erwin Putera (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was motivated by the results of observations carried out at SDN Pulorejo. namely, the problem of low learning outcomes for grade 5 students in the social studies subject, history material, was found. The low student learning outcomes are caused by students not liking and considering social studies subjects, especially history, to be difficult and boring. Therefore, in this research, a trial was carried out to improve student learning outcomes by using the interactive multimedia